2011
DOI: 10.1002/wsb.48
|View full text |Cite
|
Sign up to set email alerts
|

Effects of landscape and land‐ownership patterns on deer movements in a suburban community

Abstract: White-tailed deer (Odocoileus virginianus) have adapted to, and are thriving in, residentialsuburban landscapes. Special hunts, sharpshooting programs, and fertility control efforts have been implemented in residential communities to reduce local deer populations. For these management strategies to be effective, it is important to understand deer movement and behavior patterns in suburban landscapes. Our objectives were to quantify annual and hunt-season home-range size, and evaluate the relationships between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 24 publications
2
11
0
1
Order By: Relevance
“…Using the x ‐intercept of the correlogram as the diameter of a genetic patch (Epperson ), we can delineate a circular area of 12.6 ha centered on any given sample wherein fecal samples are more likely to be genetically similar to each other than to samples separated by greater distances. Although our data cannot be used to determine individual home range size, an area of 13 ha is smaller than the typical mean home range size reported for female deer in suburban landscapes (range of means = 25–93 ha; Cornicelli et al , Grund et al , Kilpatrick et al ), again reinforcing our findings that multiple groups of related deer may have been using the same areas. Blanchong et al () also detected patterns of relatedness within urban parks of southeast Michigan consistent with a matrilineal group structure.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Using the x ‐intercept of the correlogram as the diameter of a genetic patch (Epperson ), we can delineate a circular area of 12.6 ha centered on any given sample wherein fecal samples are more likely to be genetically similar to each other than to samples separated by greater distances. Although our data cannot be used to determine individual home range size, an area of 13 ha is smaller than the typical mean home range size reported for female deer in suburban landscapes (range of means = 25–93 ha; Cornicelli et al , Grund et al , Kilpatrick et al ), again reinforcing our findings that multiple groups of related deer may have been using the same areas. Blanchong et al () also detected patterns of relatedness within urban parks of southeast Michigan consistent with a matrilineal group structure.…”
Section: Discussionsupporting
confidence: 79%
“…However, those studies were conducted using a coarser sampling grain over larger spatial extents that spanned several counties. Our results reflect the reduced spatial scale of home ranges of white‐tailed deer in suburban landscapes (Cornicelli et al , Etter et al , Grund et al , Kilpatrick et al ). Female genotypes were significantly autocorrelated up to pairwise inter‐individual distances of only 400 m in both sampling sites.…”
Section: Discussionsupporting
confidence: 63%
“…Contrary to expectations, aggregative response was more likely to be associated with direct than indirect consumers changes habitat selection (but see e.g. Kilpatrick et al 2011). Therefore, researchers interested in habitat selection should be particularly aware that the selected habitats are likely to vary through time.…”
Section: Hypothesis 3 Are Indirect Consumers More Likely To Respond mentioning
confidence: 79%
“…Few targeted studies (TS) have explored how mast‐seeding changes habitat selection (but see e.g. Kilpatrick et al ). Therefore, researchers interested in habitat selection should be particularly aware that the selected habitats are likely to vary through time.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the fragmented nature of suburbia itself may be a driver of the observed functional response of hunters and may contribute to the observed floor on population reduction. Suburban management areas will always include properties that cannot be hunted (refugia) due to mandated set-backs from residential dwellings (Kilpatrick et al, 2011) or due to landowner opposition to deer management. A shift in deer activity toward these refugia will limit hunter success regardless of the creative solutions adopted to increase harvests (S. Williams, Connecticut Agricultural Experimental Station, unpublished data).…”
Section: Discussionmentioning
confidence: 99%